Karakteristik Gelombang Laut Indoneisa Untuk Mendukung Kegiatan Laut dan Keamanan Maritim - Ajis Nur Efendi; Muhamad Farid Geonova; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno; Desi Albert Mamahit; Trismadi (G-Tech: Jurnal Teknologi Terapan, 2023)
Wave characteristics are one of the safety factors for shipping activities. For this reason, this study aims to determine the characteristics of the waves resulting from the BMKG Inawaves Model. The data used in this research is from 2011 to 2021. The results show that the wave characteristics in Indonesia are influenced by the western season, namely December-February, which shows that high waves dominate in the Indian Ocean, North Natuna Sea and Pacific Ocean with an average wave height of 2-3 meters. In the East Season, between June and August, the average high waves dominate the Indian Ocean region with an average wave height of 2-3.5 meters. Meanwhile, in Transition Season I in March-May, the average height value that dominates the Indian Ocean region is a wave height of 2-3 meters. For the Second Transitional Season, in September-November, the wave height dominates the waters of the Indian Ocean with an average of 2-3 meters